The Distribution of Total Suspended Solid (TSS) and Sediment Texture in Matras Coastal Waters, Bangka Regency - Yesi Sagita; Aditya Pamungkas; Irma Akhrianti (Scientific Timeline, 2023)
The purpose of this study was to determine the distribution (TSS) of total suspended solids, the distribution of sediment texture and determine the relationship between TSS with currents and sediment texture with wave height. The station determination technique used is purposive sampling. The time of sampling was carried out in April 2022 in Matras Coastal Waters, Bangka Regency. TSS concentrationanalyzed in the laboratory with the total suspended solid Gravimetry method and sediment texture using pipetting method. The results obtained are the TSS concentration values ranging from 4-420 mg/l. Based on Government Rules No. 22 of 2021, several stations on Matras Beach have passed sea water quality standards. Then the mat waters have various types of sedimentary textures, namely the percentage of sand ranging from46.07-96.82%, mud percentage ranged from 1.24-22.10%, clay percentage ranged from 1.94-35.20% and fine sediment (mud + clay) ranged from 3.18-53, 93%.Then the relationship between TSS and Current Velocity shows the sig value > 0.05 meaning that the effect is not real/significant (p= 0.076) and the relationship has a weak effect (r = 0.706) and the coefficient of determination (R² = 0.498). While fine sediment with waves shows the value of sig (p= 0.675) > 0.05 meaning that it has no real or significant effect and has a weak effect (r = 0.195) and the coefficient of determination (R^2) is 0.038.